Šulgi in the Kuhdasht Plain: Bricks from a Battle Monument at the Crossroads of Western Pish-e Kuh and the Localisation of Kimaš and Ḫurti - Ghobadizadeh, Hamzeh (Zeitschrift für Assyriologie und vorderasiatische Archäologie, 2023)
Several exemplars of a brick inscription of Šulgi were found in the Kuhdasht Plain in the province of Lorestan, Iran. The reference to the destruction of Kimaš and Ḫurti provides strong evidence for the localisation of these two Zagros polities. The Ur III campaigns testify to the key role of the western Pish-e Kuh in overland traffic from the Diyala region or from Khuzestan to the central Zagros. As the source of the "copper from Kimaš," we propose the ancient mines of Deh Hosein.